The Study On The Selection Of Bridge Installation Methods For An 84-Meter Arch Bridge Based On The Hydrology Of The Cileungsi River - Halilintar, Thopan (Universitas Pahlawan Tuanku Tambusai, 2024)
84 Meter Arch Bridge Project of Cileungsi River, Bogor, West Java. The Arch Bridge is a steel bridge that connects the Cimanggis-Cibitung Toll Road. This bridge consists of 2 units of Arch Bridge series on pier A1- pier P1, which crosses the Cileungsi River, with the length of each bridge being 84 m. In this final project study, the basis for selecting the method of installing an arch bridge using the lifting method (Lifting Crane) and scaffolding (Shoring) is discussed. This method is used to ensure safety, strength and stability aspects during the installation process. This study shows that the use of the Lifting Crane and Shoring methods is very appropriate compared to using other methods.